Implementasi Profil Pelajar Pancasila Dimensi Mandiri pada Pembelajaran IPAS Kelas IV SDN Pasar Kliwon Surakarta Tahun Pelajaran 2023/2024 - Fitria Nurhasanah; Sri Mulyati; Dwi Anggareni Siwi (Pendikdas: Pendidikan Dasar, 2024)
This research aims to describe the implementation of the independent dimension of the Pancasila student profile in grade IV science and science learning at Pasar Kliwon State Elementary School, Surakarta, academic year 2023/2024. This research uses a qualitative approach with data collection tools in the form of observation, interviews and documentation. The research subjects were class students and class IV teachers. The results of the research state that the profile of Pancasila students, especially the independent dimension of students in science learning, is categorized as moderate. This means that most students have been able to apply the values of the independent dimension, namely understanding themselves and the situations they face as well as good self-regulation. Understanding themselves and the situations they face can be seen from students who feel happy and enthusiastic about learning, pay attention to the teacher's explanations, and ask friends or teachers if they don't understand the science material. Self-regulation can be seen from the behavior of students who do not joke when completing assignments, note down lesson material, use their free time to study, show initiative by preparing books and stationery before learning begins, and answer the teacher's questions without being asked, do assignments without cheating, collect assignments on time, students are also confident in expressing opinions and answering questions from the teacher, but there are also students who ask friends first before giving their answers.Â